Synthesis and Physical Characterization of Co3O4/Reduced Graphene Oxide Nanocomposites for Li Ion Batteries - Sasmaz, Merivan; Yakuphanoğlu, Fahrettin (Amer Scientific Publishers, 2016)
Reduced graphene oxide was synthesized by Hummers method. The Co3O4/reduced graphene oxide (RGO) nanocomposites were synthesized with various RGO contents via a route which includes ultra-sonication, evaporation with microwave and centrifuge. Energy disperse X-Ray (EDX) results confirmed the chemical compositions of the composites. The XRD datas were indexed as the cubic phase of Co3O4 at Fd3m space group. Typical scanning electron microscopy (SEM) images were carried out to investigate the microstructure of pure and graphene doped nanocomposites. C-O epoxy groups, tertiary C-OH groups and C=O stretching of carbonyl and carboxyl groups were observed by Fourier transform infrared spectroscopy (FTIR) measurements. The obtained results indicate that the Co3O4/reduced Graphene Oxide Nanocomposites are nanomaterials and can be used for Li Ion Batteries.
Keywords: Reduced Graphene Oxide; Nanocomposites; FTIR